Hubungan antara Ekspresi mRNA Gen Epidermal Growth Factor Receptor (EGFR) dengan Penurunan Kadar Î²-hCG Serum Pasca-evakuasi Mola Hidatidosa Komplit - PAULUS, LAURENS DAVID; HIDAYAT, YUDI MULYANA; GANDAMIHARJA, SUPRIADI (Indonesian Journal of Cancer, 2015)
In 2008, the incidence of hydatidiform mole that occurred in West Java around 1:28. Malignant transformation of Complete Hydatidiform Mole (CHM) is influenced by many factors, among others, is the expression of the epidermal growth factor receptor (EGFR). This study uses Historical Cohort to retrieve CHM patients data and trophoblastic tissue paraffin block in 2007-2012, and perform examination of Polymerase chain reaction.Results of the study: 40 CHM patients, 24 with EGFR (-) and 16 with EGFR (+), at 12 weeks monitoring post evacuation using the Mochizuki regression curve was not obtained persistent mole in the group with EGFR (-), while the group of EGFR (+), all showed an increase in Î²-hCG levels. Relative risk (RR) of 3.4 in the CHM group with EGFR (+) into a persistent mole compared with EGFR (-) at 6th week and RR of 13.0 in CHM group with EGFR (+) into a persistent mole compared with EGFR (-) at 8th week. The conclusion of this study demonstrate the suitability of the hypothesis that the higher mRNA gene expression of EGFR, the slower decrease in serum levels of Î²-hCG after CHM evacuation and expression EGFR (+) may be a predictor of the occurrence of persistent mole.Â Pada 2008, insiden mola hidatidosa (MH) yang terjadi di Jawa Barat sekitar 1:28. Transformasi keganasan dari mola hidatidosa komplit (MHK) dipengaruhi oleh banyak faktor, antara lain ekspresi Epidermal Growth Factor Receptor (EGFR). Penelitian ini menggunakan metode historical cohort dengan mengambil data dan parafin block jaringan trofoblas pasien MHK tahun 2007â2012, dan dilakukan pemeriksaan POLYMERASE CHAIN REACTion. Hasil penelitian menunjukkan dari 40 pasien MHK, 24 di antaranya EGFR (-) dan 16 EGFR (+) pada 12 minggu pascaevakuasi menggunakan kurva regresi Mochizuki. Tidak didapatkan mola persisten pada kelompok EGFR (-), sedangkan kelompok EGFR (+) semuanya menunjukkan peningkatan Î²-hCG (mola persisten). Risiko relatif (RR) sebesar 3,4 pada EGFR (+) menjadi mola persisten dibandingkan dengan EGFR (-) pada minggu ke-6 dan RR sebesar 13,0 pada EGFR (+) menjadi mola persisten dibandingkan dengan EGFR (-) pada minggu ke-8. Hasil penelitian ini menunjukkan kesesuaian dengan hipotesis bahwa semakin tinggi ekspresi EGFR maka semakin lambat penurunan kadar Î²-hCG serum pasca-evakuasi MHK. Ekspresi EGFR dapat menjadi prediktor terjadinya mola persisten.